The “Sanctification” and “Desacralization” of Humanity: Tracing the Rise and Fall of Liberalism and Seeking New Paths Forward - HE, Zhijian (Journal of Research for Christianity in China (JRCC), 2025)
The affirmation of “individual rights” constitutes one of the core tenets of liberalism. While it laid the foundation for liberalism's initial rise and propelled the development and evolution of modern society, it has also become the root cause of its gradual decline amid intensifying secularization and pluralistic tendencies. This paper seeks to trace the intellectual trajectory of liberalism in both Chinese and Western contexts by examining the “sanctification” of the human being. Building upon this analysis, it offers preliminary reflections on potential pathways forward. A preliminary conclusion emerges: Western liberalism, centered on “individual rights,” has increasingly exhibited extremist tendencies amid deepening secularization, rendering it ill-equipped to address spiritual crises. Meanwhile, Chinese liberalism, anchored in the “nation/ethnic group,” ultimately diverged from its founding principles through the sanctification of a symbolic “people.” Neither represents the future direction of liberalism. The ideal path lies in reconciling liberalism with a “transcendent spirit”—achieved by respecting and affirming the rights of the individual while simultaneously ‘desacralizing’ humanity to some degree. In other words, this entails vigilance and reflection on humanity's “dark spirit” and “rationalism.”